DIGITALISASI LAPORAN TRANSAKSI KEUANGAN UMKM SEKTOR KULINER BERDASARKAN “SAK EMKM” - F.X. Kurniawan Tjakrawala; Ricky Sinaga; Louis Joshua (PROSIDING SERINA, 2021)
The purpose of community service engagement is to provide counseling/training on aspects of financial transaction reporting in the digital ecosystem based on msme’s standard in order to increase adequate financial literacy for msme entrepreneur, especially the culinary industry sector. The owner of the Restaurant "Seafood67 & Soto Lamongan" was still became the partner of this service engagement. The results of surveys and discussions with partners provide an illustration that the owner of the restaurant has not been able to carry out an accounting system in accordance with applicable standards; experiencing difficulties in dealing with financial institutions because they do not yet have adequate financial reports; still report income taxes using the final rate because they do not yet have an adequate bookkeeping system. The method used in this community service activity is the lecture method, question and answer and also the practice of digitally inputting transaction data in accordance with msme’s standard. The results of this community service engagement are useful because they are able to provide concrete solutions to the partner’s problems. This community service activity also involved students from the FEB UNTAR that’s intended to exercise the ability to analyze the real problems/facts in society. In addition, the participation of students also had a positive impact on the accreditation of the study program in FEB UNTAR. This community service engagement also produces output in the form of scientific articles for publication in the proceedings of scientific meetings.Tujuan dari aktivitas Pengabdian kepada Masyarakat (PKM) adalah mengadakan penyuluhan/pelatihan mengenai aspek pelaporan transaksi keuangan dalam ekosistem digital berdasarkan SAK EMKM guna meningkatkan literasi keuangan yang memadai bagi pelaku UMKM khususnya sektor industri kuliner.Mitra PKM pada periode ini adalah Rumah Makan “Seafood67 & Soto Lamongan”. Hasil survey maupun diskusi dengan mitra memberikan gambaran bahwa pemilik rumah makan tersebut belum dapat menyelengarakan sistem pembukuan sesuai dengan standar yang berlaku; mengalami kendala berhubungan dengan lembaga pembiayaan karena belum memiliki laporan keuangan yang memadai; masih melaporkan pajak menggunakan norma penghitungan karena belum punya sistem pembukuan yang memadai. Metode yang dipakai dalam PKM ini adalah metode ceramah, tanya-jawab dan juga praktek input data transaksi secara digital sesuai dengan SAK EMKM. Hasil dari PKM ini bermanfaat karena mampu memberi solusi konkrit atas permasalahan yang dialami oleh mitra. Kegiatan PKM ini juga melibatkan mahasiswa FEB UNTAR. Keterlibatan mahasiswa dimaksudkan melatih kemampuan analsis terhadap masalah riil/fakta di masyarakat. Selain itu keikutsertaan mahasiswa prodi PPAk juga berdampak positif terhadap akreditasi program studi pada FEB Untar. PKM ini juga menghasilkan luaran berupa artikel ilmiah untuk keperluan publikasi pada prosiding pertemuan ilmiah.